Automatic planning of the acquisition of cardiac MR images - Jackson, C; Robson, M; Francis, J; Noble, J (2003)
A method to automatically plan acquisition of images aligned with the cardiac axes is presented. The average short axis orientation of images acquired from a group of fifty adult patients is calculated. Localiser images are acquired with this mean orientation. These images are automatically segmented using the Expectation Maximisation (EM) algorithm. The borders of the left and right ventricle blood pools are then found by analysing the properties of the segmented regions. Data points on these borders are used to provide an estimate of the orientation of the cardiac axes. © Springer-Verlag Berlin Heidelberg 2003.